Visual CAPTCHA application in linguistic cryptography. (4th December 2017) - Ogiela, Urszula; Takizawa, Makoto; Ogiela, Lidia
Summary: This paper presents an idea of linguistic cryptography and linguistic techniques for data analysis. The main aspects are using parts of divided information to reconstruct them. Linguistic techniques dedicated to cryptography, as well as secret splitting and sharing, are very useful to secure all information and all parts of them. Very important aspects of cryptographic algorithms are played by techniques of data division as well as data splitting and information sharing algorithms. Those methods allow the distributed data within a different selected group of secret trustees. In this paper, authors described algorithms of using those methods for linguistic data sharing techniques. In those methods, CAPTCHA analysis plays an important role. All secret parts of information can be written by using any parts of the selected CAPTCHA procedures.